Awareness, Knowledge, and Acceptance of Haematopoietic Stem Cell Transplantation for Sickle Cell Anaemia in Nigeria. (27th September 2016) - Adediran, Adewumi; Kagu, Modu Baba; Wakama, Tamunomieibi; Babadoko, Aliyu Ahmadu; Damulak, Dapus Obadiah; Ocheni, Sunday; Asuquo, Marcus Inyama
Abstract : Background. Sickle cell anaemia (SCA) is an inherited condition whose clinical manifestations arise from the tendency of haemoglobin to polymerize and deform red blood cells into characteristic sickle shape. Allogeneic bone marrow transplantation offers a cure. The aim of this study was to determine the level of awareness, knowledge, and acceptance of this beneficial procedure in Nigeria. Materials and Methods. This multicentre cross-sectional study was conducted in 7 tertiary hospitals in Nigeria in 2015. Approval was obtained from each institution's research and ethics committee. A pretested structured questionnaire was administered to respondents aged 18 years and above and to the parents or guardians of those below 18 years of age. Results. There were 265 respondents comprising 120 males and 145 females. One hundred and seventy-one (64.5%) respondents were aware of BMT for the treatment of SCA. About 67.8% (116 of 171) of those who were aware believed SCA can be cured with BMT (p = 0.001 ) and 49.7% (85 of 171) of the respondents accepted BMT (p = 0.001 ). Conclusion. Awareness of BMT in Nigeria is low when compared with reports from developed countries. The knowledge is poor and acceptance is low. With adequate information, improved education, and psychological support, more Nigerians will embrace BMT.